Feedback regulation of methyl methanesulfonate and ultraviolet-sensitive gene clone 81 via ATM/Chk2 pathway contributes to the resistance of MCF-7 breast cancer cells to cisplatin - Juan Lv; Ying Qian; Xiaoyan Ni; Xiuping Xu; Xuejun Dong (Tumor Biology)
The methyl methanesulfonate and ultraviolet-sensitive gene clone 81 protein is a structure-specific nuclease that plays important roles in DNA replication and repair. Knockdown of methyl methanesulfonate and ultraviolet-sensitive gene clone 81 has been found to sensitize cancer cells to chemotherapy. However, the underlying molecular mechanism is not well understood. We found that methyl methanesulfonate and ultraviolet-sensitive gene clone 81 was upregulated and the ATM/Chk2 pathway was activated at the same time when MCF-7 cells were treated with cisplatin. By using lentivirus targeting methyl methanesulfonate and ultraviolet-sensitive gene clone 81 gene, we showed that knockdown of methyl methanesulfonate and ultraviolet-sensitive gene clone 81 enhanced cell apoptosis and inhibited cell proliferation in MCF-7 cells under cisplatin treatment. Abrogation of ATM/Chk2 pathway inhibited cell viability in MCF-7 cells in response to cisplatin. Importantly, we revealed that ATM/Chk2 was required for the upregulation of methyl methanesulfonate and ultraviolet-sensitive gene clone 81, and knockdown of methyl methanesulfonate and ultraviolet-sensitive gene clone 81 resulted in inactivation of ATM/Chk2 pathway in response to cisplatin. Meanwhile, knockdown of methyl methanesulfonate and ultraviolet-sensitive gene clone 81 activated the p53/Bcl-2 pathway in response to cisplatin. These data suggest that the ATM/Chk2 may promote the repair of DNA damage caused by cisplatin by sustaining methyl methanesulfonate and ultraviolet-sensitive gene clone 81, and the double-strand breaks generated by methyl methanesulfonate and ultraviolet-sensitive gene clone 81 may activate the ATM/Chk2 pathway in turn, which provide a novel mechanism of how methyl methanesulfonate and ultraviolet-sensitive gene clone 81 modulates DNA damage response and repair.